NET CITIZENS' LANGUAGE POETTY IN INSTAGRAM COMMENTS NW ARTISTS - _, Rissa; Nofrita, Misra (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STKIP Ahlussunnah, 2025)
This study aims to analyze the politeness in netizens' language within comments on the Instagram account of artist NW. The study employs Leech's (1983) politeness principles, which include seven maxims: tact, generosity, approbation, modesty, agreement, sympathy, and consideration. A qualitative descriptive method was used, with data collected from netizen comments on NW's Instagram posts throughout 2024. The analysis revealed that the approbation maxim dominated (23 data points) compared to other maxims, such as sympathy (10 data points), agreement (4 data points), and tact, generosity, and modesty, which each had 1 data point, while the consideration maxim was not found. The dominance of the approbation maxim is attributed to Instagram's nature as a platform that encourages expressions of admiration and NW's positive image as a public figure. This study highlights the importance of politeness in language use during social media interactions to foster harmonious communication and reflect social norms. Furthermore, it provides insights into the influence of Indonesian cultural politeness norms in digital spaces. By understanding politeness principles, it is expected that netizens can communicate more ethically and effectively on social media.